PARADOXES OF THE OTHER: (POST)COLONIAL RACISM, RACIAL DIFFERENCE, STEREOTYPE-AS-FETISH - Hook, Derek (PINS-Psychology in Society, 2026)
This paper draws on the work of Homi Bhabha to mount an explanation for a facet of (post)colonial racism, the "paradox of otherness" as exemplified in the racial stereotype The paradox in question operates at the levels of discourse and identification alike As a mode of discourse the stereotype functions to exaggerate difference of the other, whilst nevertheless attempting to produce them as a stable, fully knowable object. As mode of identification, the stereotype operates a series of mutually exclusive categories differentiating self and other which unintentionally nevertheless relies upon a grid of samenesses. These two paradoxes follow a similar movement: an oscillation, at the level of discourse, between attempts to generate and contain anxiety, a wavering, at the level of identification, between radical difference and prospective likeness. Bhabha provides a structural and functional analogue with which to account for this double movement of otherness: Freud’s model of fetishism. This is an analogue that both enables us to foreground the operations of displacement and condensation in racist stereotyping, and to draw a series of conclusions about the effective functioning of discursive and affective economies of racism.